Development and Evaluation of the Shared Decision Making Process Scale: A Short Patient-Reported Measure. (February 2021) - Valentine, K. D.; Vo, Ha; Fowler, Floyd J.; Brodney, Suzanne; Barry, Michael J.; Sepucha, Karen R.
Background: The Shared Decision Making (SDM) Process scale is a short patient-reported measure of the amount of SDM that occurs around a medical decision. SDM Process items have been used previously in studies of surgical decision making and exhibited discriminant and construct validity. Method: Secondary data analysis was conducted across 8 studies of 11 surgical conditions with 3965 responses. Each study contained SDM Process items that assessed the discussion of options, pros and cons, and preferences. Item wording, content, and number of items varied, as did inclusion of measures assessing decision quality, decisional conflict (SURE scale), and regret. Several approaches for scoring, weighting, and the number of items were compared to identify an optimal approach. Optimal SDM Process scores were compared with measures of decision quality, conflict, and regret to examine construct validity; meta-analysis generated summary results. Results: Although all versions of the scale were highly correlated, a short, partial credit, equally weighted version of the scale showed favorable properties. Overall, higher SDM Process scores were related to higher decision quality ( d = 0.18, P = 0.029), higher SURE scale scores ( d = 0.57, P < 0.001), and lower decision regret ( d = −0.34, P < 0.001). Significant heterogeneity was present in all validity analyses. Limitations: Included studies all focused on surgical decisions, several had small sample sizes, and many were retrospective. Conclusion: SDM Process scores showed resilience to coding changes, and a scheme using the short, partial credit, with equal weights was adopted. The SDM Process scores demonstrated a small, positive relationship with decision quality and were consistently related to lower decision conflict and less regret, providing evidence of validity across several surgical decisions.